Synthesis, single crystal analysis, biological and docking evaluation of tetrazole derivatives. Issue 9 (September 2018) - Aziz, Hamid; Saeed, Aamer; Jabeen, Farukh; Din, Noor ud; Flörke, Ulrich
Abstract: Tetrazoles are conjugated nitrogen-rich heterocycles considered as bio-isosteres of carboxylic acids. Tetrazoles owing to their conjugated structures serve as biologically relevant potent scaffolds. The present research paper reports the successful synthesis and single crystal analysis of three different tetrazole derivatives (2, 4, 6) . The synthesized tetrazole derivatives were evaluated for their possible cytotoxicity LD50 (52.89, 49.33, 17.28 μg/ml) and antileishmanial activities IC50 (0.166, 10, 5.0 μg/ml). Moreover, molecular docking studies were performed to determine the possible interaction sites of the tetrazole derivatives (2, 4, 6) with TryR, an enzyme involved in the redox metabolism of the Leishmania parasite. Docking computations demonstrates that the tetrazole derivatives (2, 4, 6) established prominent binding interactions with the key residues of the TryR and possess the potential to effectively inhibit the catalytic activities of the enzyme. The results suggested that the synthesized tetrazole derivative (2, 4, 6) can be possible hit candidates which can be tested further against amastigote stage of parasite and then in an animal model of leishmaniasis.